Wnts in action: from synapse formation to synaptic maintenance - Salinas, Patricia C. (Frontiers in Cellular Neuroscience, 2013)
A proper balance between synapse assembly and disassembly is crucial for the formation of functional neuronal circuits and synaptic plasticity in the adult brain. During development, synaptogenesis generates a vast excess of synapses, which are subsequently eliminated. Importantly, aberrant synaptic disassembly during development underpins many neurological disorders. Wnt secreted proteins are robust synaptogenic factors that regulate synapse assembly and function in the developing and mature brain. Recent studies show that Wnt blockade with the antagonist Dickkopf-1 (Dkk1) induces the rapid disassembly of synapses in mature neurons. Importantly, Dkk1 mediates synaptic loss induced by Amyloid-ß, a key pathogenic molecule in Alzheimer’s disease (AD). These findings provide new insights into the potential contribution of dysfunctional Wnt signaling to synaptic loss observed in neurodegenerative diseases. In this review, we discuss the role of Wnt signaling in vertebrate synaptic assembly, function and maintenance, and consider how dysfunction of Wnt signaling could contribute to synaptic disassembly in neurodegenerative diseases such as AD.